The biomechanical analysis of load characteristics during discus throws with various weight implements - Hirose, K.; Maeda, K.; Noguchi, Y.; Byun, K. O. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to clarify the load characteristics during throw with various weight discuses. Fourteen male discus throwers were analysed by using three-dimensional motion analyses. The maximum forces throughout the throw of the lighter discus (1.5 kg and 1.75 kg) were significantly lower than that of the competition weight discus (2.0 kg). However, the maximum force throughout the throw of the heavier discus (2.25 kg) was not significantly higher than that of the competition weight discus (2.0 kg). Focusing on the turn phases, the value of the forces were lower in the throw of the lighter discus. On the other hand, the maximum force in the throw of the heavier discus (2.25 kg) was greater than that of the competition weight discus (2.0 kg), except before release. This indicates that throw with various weight discuses changed load property.